Constructivism-Based Science Practicum In Philosophy Perspective - Bakhtiar Ardiansyah; Muhammad Sarjan; Agus Muliadi; Asrul Azizi; Hamidi Hamidi; Iswari Fauzi; Muhammad Yamin; Muh Zaini Hasanul Muttaqin; Mulia Rasyidi; Rindu Rahmatiah; Sudirman sudirman; Yusran Khery (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2022)
This article aims to describe philosophically related to Constructivism-Based Science Practicum. This article uses a qualitative descriptive approach. Information was obtained based on observations, experience, and a literature review from several journal literature. Philosophical studies can strengthen ontology related to the nature of constructivism-based science practicum, a science practicum that leads to constructing students' thinking so that knowledge, skills, and attitudes are increasing. Epistemologically (usefulness), constructivism-based science practicum can improve students' concepts and skills in understanding science concepts. Axiologically (Universal values) constructivism-based science practicum can be obtained from science practicum activities that shape scientific attitudes and behaviour in general.